2015
DOI: 10.3390/molecules20034848
|View full text |Cite
|
Sign up to set email alerts
|

QSAR-Assisted Virtual Screening of Lead-Like Molecules from Marine and Microbial Natural Sources for Antitumor and Antibiotic Drug Discovery

Abstract: A Quantitative Structure-Activity Relationship (QSAR) approach for classification was used for the prediction of compounds as active/inactive relatively to overall biological activity, antitumor and antibiotic activities using a data set of 1746 compounds from PubChem with empirical CDK descriptors and semi-empirical quantum-chemical descriptors. A data set of 183 active pharmaceutical ingredients was additionally used for the external validation of the best models. The best classification models for antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…Furthermore, Log P is one of the most important molecular descriptors since it is highly correlated with lipophilicity, thus, more lipophilic molecules are often discontinued from drug development and are frequently connected to toxicity issues . Besides MW and Log P, we recently reported that the topological descriptor MDEO‐12 (molecular distance edge between primary and secondary oxygen atoms), the electronic descriptor TopoPSA (topological polar surface area) and the quantum‐chemical descriptor HOMO (highest occupied molecular orbital energy), have a remarkable performance in discriminating antitumor, antibiotic and overall biological lead‐like compounds, respectively.…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, Log P is one of the most important molecular descriptors since it is highly correlated with lipophilicity, thus, more lipophilic molecules are often discontinued from drug development and are frequently connected to toxicity issues . Besides MW and Log P, we recently reported that the topological descriptor MDEO‐12 (molecular distance edge between primary and secondary oxygen atoms), the electronic descriptor TopoPSA (topological polar surface area) and the quantum‐chemical descriptor HOMO (highest occupied molecular orbital energy), have a remarkable performance in discriminating antitumor, antibiotic and overall biological lead‐like compounds, respectively.…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, LogP is one of the most important molecular descriptors since it is highly correlated with lipophilicity, thus, more lipophilic molecules are often discontinued from drug development and are frequently related to toxicity issues [ 45 ]. Besides MW and LogP, we recently reported that the topological descriptor MDEO-12 (molecular distance edge between primary and secondary oxygen atoms) [ 46 ], the electronic descriptor TopoPSA (topologicalpolar surface area) [ 46 ] and the quantum-chemical descriptor HOMO (highest occupied molecular orbital energy) [ 47 ], have a remarkable performance in discriminating antitumor, antibiotic and overall biological lead-like compounds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, some research groups focus their work on the discovery of antibiotics in nature. [70][71][72] Thai et al have developed a linear QSAR model to analyze a collection of 182 flavonoids and the Chinese Medicine Database searching for new S. aureus NorA pump inhibitors. 70 Similarly, Pereira et al developed a QSAR model for the search of antibacterial compounds in PubChem (1,804 compounds) and the AntiMarin Database (418 compounds).…”
Section: Qsar In Antibacterial Compound Developmentmentioning
confidence: 99%